Challenges in preoperative diagnosis of glossopharyngeal nerve schwannoma: own findings analysis - Skobska, O.E.; Sirko, A.H.; Zemskova, O.V.; Lisianyi, O.M.; Popovych, I.O.; Malyi, R.R. (Medicni Perspektivi, 2022)
Medical history, disease onset, clinical symptoms, and results of neuroimaging of 14 glossopharyngeal schwannoma patients, who were examined and treated in the Subtentorial Neurooncology Department of the State Institution, Romodanov Institute of Neurosurgery of the NAMS of Ukraine (8 patients) and the Neurosurgery Department No. 2 of the Municipal Enterprise, Mechnikov Dnipropetrovsk Regional Clinical Hospital of Dnipropetrovsk Regional Council (6 patients) in 2018 to 2021 have been analyzed in details. The study inclusion criteria were as follows: patient’s age over 18, presence of unilateral primary glossopharyngeal nerve schwannoma. Our study showed that most of clinical signs and symptoms of the glossopharyngeal nerve schwannoma are associated with otolaryngological disorders (such as hearing loss, tinnitus, hoarseness, or dizziness) or cerebellar disorders (such as ataxia, nystagmus, or dizziness). Neuroimaging cerebellopontine angle tumors diagnosis must include brain computed tomography (with mandatory assessment of the state of jugular foramen and internal auditory canal) and IV contrast brain magnetic resonance tomography and inclusion of high-resolution sequences, gradient echo (3D CISS, DRIVE, TRUFFI, B-FFE) with the aim of better visualization and differentiation of various cerebellopontine angle cranial nerves. The study demonstrates the complexity of a reliable preoperative diagnosis when using standard diagnostic tools. Preoperative jugular foramen and cerebellopontine angle tumors diagnosis should be based on a systematic approach and include a comparison of results of comprehensive clinical and instrumental examination and neuroimaging studies.